Effect of premolar extraction and anchorage type for orthodontic space closure on upper airway dimensions and position of hyoid bone in adults: a retrospective cephalometric assessment - Mortezai, Omid; Shalli, Zeynab; Tofangchiha, Maryam; Alizadeh, Ahad; Pagnoni, Francesco; Reda, Rodolfo; Testarelli, Luca (PeerJ, 2023)
Background This study aimed to assess the effect of premolar extraction and anchorage type for orthodontic space closure on upper airway dimensions and position of hyoid bone in adults by cephalometric assessment. Methods This retrospective study was conducted on 142 cephalograms of patients who underwent orthodontic treatment with premolar extraction in four groups of (I) 40 class I patients with bimaxillary protrusion and maximum anchorage, (II) 40 class I patients with moderate crowding and anchorage, (III) 40 class II patients with maximum anchorage, and (IV) 22 skeletal class III patients with maximum anchorage. The dimensions of the nasopharynx, velopharynx, oropharynx, and hypopharynx, and hyoid bone position were assessed on pre- and postoperative lateral cephalograms using AudaxCeph v6.1.4.3951 software. Data were analyzed by the Chi-square test, paired t-test, and Pearson’s correlation test (alpha = 0.05). Results A significant reduction in oropharyngeal, velopharyngeal, and hypopharyngeal airway dimensions was noted in groups I, III, and IV (P < 0.001), which was correlated with the magnitude of retraction of upper and lower incisors (r = 0.6 − 0.8). In group II, a significant increase was observed in oropharyngeal and velopharyngeal dimensions (P < 0.001). A significant increase in nasopharyngeal dimensions occurred in all groups (P < 0.001). Also, in groups I and III, the position of hyoid bone changed downwards and backwards, which was correlated with reduction in airway dimensions (r = 0.4 − 0.6). Conclusion According to the present results, extraction orthodontic treatment affects upper airway dimensions and hyoid bone position. Maximum anchorage decreases airway dimensions while moderate anchorage increases airway dimensions.
Keywords: Space closure; Upper Airway dimensions; Hyoid bone; Cephalometric; Retrospettive study